Sound production, hearing sensitivity, and in‐depth study of the sound‐producing muscles in the cowfish (Lactoria cornuta). Issue 4 (4th November 2020) - Parmentier, Eric; Marucco Fuentes, Erica; Millot, Morgane; Raick, Xavier; Thiry, Marc
Abstract: The ability to produce sounds has been reported in various Ostraciidae but not deeply studied. In some Ostracion species, two different sound‐producing muscles allow these boxfishes to produce two different kinds of sounds in a sequence. This study investigates sound production in another Indo‐Pacific species, the longhorn cowfish Lactoria cornuta that also possesses two pairs of sonic muscles associated with the swim bladder: extrinsic sonic muscles (ESMs) and intrinsic sonic muscles (ISMs). The cowfish produces two kinds of sounds called hums and clicks. Hums are made of trains of low amplitude pulses that last for long periods of time, suggesting that they are produced by fatigue‐resistant muscles, whereas clicks correspond to shorter sounds with greater amplitude than the hums, suggesting that they result from more powerful contractions. Ultra‐structural differences are found between extrinsic and intrinsic sonic muscles. According to features such as long sarcomeres, long I‐bands, a high number of mitochondria, and a proliferation of sarcoplasmic reticulum (SR), ESMs would be able to produce fast, strong, and short contractions corresponding to clicks (the shortest sounds with the greatest amplitude). ISMs have the thinnest cells, the smallest number of myofilaments that have long I‐bands, the highest volume of mitochondria, and well‐developed SR supporting these muscles; these features should generate fast and prolonged contractions that could correspond to the hums that can be produced over long periods of time. A concluding figure shows clear comparisons of the different fibers that were studied in L. cornuta . This study also compared the call features of each sound with the cowfish's hearing ability and supports L. cornuta was more sensitive to frequencies ranging between at least 100 and 400 Hz with thresholds of 128–143 dB re 1 µPa over this range, meaning that they are sensitive to the frequencies produced by conspecifics. Abstract : The longhorn cowfish Lactoria cornuta possesses two pairs of sonic muscles and produces two kinds of sounds called hums and clicks. Hums are made of long trains of low amplitude pulses suggesting that they are made by fatigue‐resistant muscles, whereas clicks result from powerful contractions. Deep histological investigations highlight both muscles are fast muscles, but they possess anatomical features allowing to relate reasonably each of them to a kind of sound.